Carbon-coated sulfur-titanium niobium oxide composite positive electrode material and preparation method and application thereof
By using high-conductivity titanium niobium oxide in the positive electrode material of lithium sulfur battery and combining it with elemental sulfur and carrying out surface carbon coating treatment, the problem of poor rate performance and cycle stability of lithium sulfur battery is solved, and efficient conductivity improvement and energy density maintenance are achieved.
Patent Information
- Application Number
- CN202510073656.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The rate performance and cycle stability of lithium-sulfur batteries are poor, and the poor conductivity of elemental sulfur leads to increased impedance and severe polarization of the battery. The sulfur positive electrode will produce volume expansion and polysulfide shuttle effects during the discharge process, resulting in low charge and discharge efficiency.
High conductivity polar titanium niobium oxide (TiNb2O7) is used as a carrier, and the elemental sulfur is compounded by solvent thermal sulfur storage method, and the surface of the composite material is subjected to low-temperature and ultra-low dose surface carbon coating treatment to form a carbon-coated sulfur-titanium niobium oxide composite positive electrode material.
The electronic conductivity of the composite material is significantly improved, the volume expansion of the sulfur positive electrode and the polysulfide shuttle problems are suppressed, the rate performance and cycle stability of lithium-sulfur batteries are improved, and the energy density is maintained.
Smart Images

Figure CN119920879A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal battery materials, and in particular to a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, a preparation method and applications thereof. Background Art
[0002] Lithium-ion batteries have excellent electrochemical properties and are widely used in electronic equipment, transportation, energy storage and other fields. However, due to the theoretical specific capacity of positive and negative electrode materials, the energy density of conventional lithium-ion batteries is difficult to exceed 300Wh / kg. In order to meet the technical requirements of portable electronic devices and electric vehicles for lightweight and long battery life, it is extremely important to develop secondary batteries with high specific energy. Lithium-sulfur batteries have attracted much attention for their high energy density and environmental protection characteristics.
[0003] Compared with traditional lithium-ion batteries, the elemental sulfur of the positive electrode active material of lithium-sulfur batteries is abundant on Earth and has the characteristics of low price and green environmental protection. 2 S 2 / Li 2 The conductivity of sulfur is very poor, which causes problems such as increased battery impedance and severe polarization, thereby reducing the energy conversion efficiency of the battery and failing to meet the requirements of high-rate charge and discharge. At the same time, during the discharge process, the sulfur cathode will not only expand in volume, causing the electrode structure to collapse, but also produce a large amount of polysulfides, causing a "shuttle effect", resulting in low charge and discharge efficiency. Therefore, the rate performance and cycle stability of lithium-sulfur batteries are poor. In order to solve this problem, strategies such as composites with conductive carbon materials or metal oxide materials are usually adopted to modify the elemental sulfur cathode material. Usually, elemental sulfur and TiO 2 , Fe 2 O 3 The metal oxides such as niobium and niobium are compounded to enhance the adsorption capacity of polysulfides and improve the cycle stability of lithium-sulfur batteries. However, when metal oxide materials are compounded with sulfur, since they do not provide reversible charge and discharge capacity within the operating voltage range of lithium-sulfur batteries, the gram-specific capacity of the composite material will be reduced, which is not conducive to improving the energy density of lithium-sulfur batteries.
[0004] At the same time, the composite of elemental sulfur and carbon materials can effectively improve the conductivity of elemental sulfur, and can inhibit the volume expansion of sulfur during the charging and discharging process and inhibit the shuttle effect during the discharge process. However, the preparation form of conventional sulfur-carbon composite materials is generally mechanical mixing or carbon as a carrier sulfurization. These two methods of composite usually require the use of a higher content of carbon material (>30wt.%) to improve the electronic conductivity of the positive electrode composite material, thereby improving the rate performance of the battery. Although the increase in carbon content can improve conductivity, carbon does not provide additional capacity. Therefore, the active substance sulfur will also reduce the energy density of the lithium-sulfur battery after being composited with more carbon. On the other hand, the intermolecular bonding between non-polar carbon elements and polar polysulfides is weak, and cannot solve the problem of polysulfides generated during the discharge of the sulfur positive electrode. Summary of the invention
[0005] In order to solve the deficiencies of elemental sulfur positive electrode materials in rate performance and cycle stability, the present invention provides a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, a preparation method and applications thereof.
[0006] The present invention uses high-conductivity polar titanium niobium oxide as a carrier, and through a solvent thermal sulfur storage method, it is compounded with elemental sulfur, which effectively improves the conductivity of elemental sulfur and inhibits the volume expansion of elemental sulfur during discharge and the problem of polysulfide shuttling. In order to further improve the electronic conductivity of the composite material, plasma technology is used to perform low-temperature and ultra-low-dose surface carbon coating treatment on the surface of the sulfur-titanium niobium oxide composite material. The carbon-coated sulfur-titanium niobium oxide composite positive electrode material finally obtained has high ionic and electronic conductivity, and through the binding of the polar titanium niobium oxide inside the composite material and the physical barrier of the external carbon material, the polysulfide can be confined inside the composite positive electrode material, and all chemical reactions are carried out on the surface of the high-conductivity material, which provides an effective way to improve the charging and discharging efficiency and overall performance of the battery.
[0007] The specific technical solutions adopted by the present invention to solve the above technical problems are as follows:
[0008] The present invention provides a method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, comprising the following steps:
[0009] (1) uniformly mixing a titanium precursor and a niobium precursor in an organic solvent at room temperature, adding an additive, pouring the mixed solution of the three into an inner container, and then placing the inner container into a reaction kettle to perform a solvothermal reaction;
[0010] (2) calcining the obtained precipitate to obtain titanium niobium oxide material;
[0011] (3) uniformly mixing elemental sulfur and titanium niobium oxide in an organic solvent at room temperature, and pouring the mixture into a reactor to perform a solvent thermal reaction. After the reaction, the mixture is filtered and dried to obtain a sulfur-titanium niobium oxide composite material;
[0012] (4) The benzene carbon source is sealed in a glass container with an air valve, the sulfur-titanium niobium oxide composite material obtained in step (3) is placed in a plasma reaction device, and a carbon material is coated on the surface of the sulfur-titanium niobium oxide composite material by plasma enhanced chemical vapor deposition to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material.
[0013] By adopting the above technical solution, the present invention adopts high conductivity polar titanium niobium oxide (TiNb 2 O 7 ) as a carrier, and through the solvent thermal sulfur storage method, it is compounded with elemental sulfur to obtain a sulfur-titanium niobium oxide composite material. At the same time, in order to further improve the electronic conductivity of the composite material, plasma technology is used to perform low-content carbon coating on the surface of the composite material, which significantly improves the electronic conductivity of the composite material. The carbon-coated sulfur-titanium niobium oxide composite positive electrode material finally obtained not only has high coulombic efficiency and excellent rate performance, but also has significantly improved cycle stability, and has broad application prospects in the field of lithium metal batteries.
[0014] The following is a preferred technical solution of the present invention:
[0015] Preferably, in step (1), the titanium precursor is at least one of tetrabutyl titanate, tetraethyl titanate and titanium dioxide; the niobium precursor is at least one of niobium pentachloride, niobium oxalate and niobium pentoxide; and the additive is at least one of polystyrene, polyvinyl alcohol and polylactic acid.
[0016] Preferably, in step (1), the purity of the titanium precursor is ≥98%, and the purity of the niobium precursor is ≥99%.
[0017] Preferably, in step (1), the molar ratio of the titanium precursor to the niobium precursor is 1:2.
[0018] Preferably, in step (1), the amount of the additive added is 3-5 wt.% of the total mass of the titanium precursor and the niobium precursor. More preferably, the purity of the additive is ≥96%.
[0019] Preferably, in step (1), the conditions for the solvent thermal reaction are: the organic solvent is at least one of ethanol, ethylene glycol, isopropanol and butanol, the reaction temperature is 140-180° C., the reaction time is 8-20 h, and the feed-liquid mass ratio is 1:4-1:8.
[0020] Preferably, in step (2), the precipitate is washed multiple times with deionized water and dried, and then calcined using a muffle furnace. More preferably, the drying condition is 60-120° C. for 1-12 hours.
[0021] Preferably, in step (2), the calcination conditions are: calcination temperature is 700-900° C., calcination time is 5-10 h, and heating rate is 2-5° C. / min.
[0022] Preferably, in step (2), the titanium niobium oxide material is TiNb 2 O 7 , with a specific surface area of 100 to 300 m 2 / g, the pore size is 1 to 50 nm, and the particle size is 2 to 8 μm.
[0023] Preferably, in step (3), the mass ratio of elemental sulfur to titanium niobium oxide is 7:3 to 9:1.
[0024] Preferably, in step (3), the conditions for the solvent thermal reaction are: the organic solvent is at least one of ethanol, ethylene glycol, isopropanol, butanol and carbon disulfide, the reaction temperature is 140-180°C, the reaction time is 12-24h, and the material-liquid mass ratio is 1:4-1:8.
[0025] Preferably, in step (3), after the solvent thermal reaction, suction filtration and drying are performed in sequence. More preferably, the drying condition is drying at 60-100° C. for 5-14 hours.
[0026] Preferably, in step (4), the benzene-based carbon source includes at least one of benzene, toluene, ethylbenzene and xylene. Benzene-based substances contain benzene rings and have unique conjugated double bonds, which make it easier to form highly conductive carbon materials during the plasma reaction.
[0027] Preferably, in step (4), the reaction conditions of the plasma enhanced chemical vapor deposition method include: evacuating to a vacuum degree of 10 to 30 Pa, heating temperature of 30 to 150° C., radio frequency power of 100 to 500 W, and reaction time of 5 to 30 min.
[0028] Preferably, in step (4), the carbon content in the carbon-coated sulfur-titanium niobium oxide composite positive electrode material is 2-5 wt.%. More preferably, the thickness of the carbon material coated on the surface of the sulfur-titanium niobium oxide composite material is 10-20 nm.
[0029] Preferably, in step (4), coating the carbon material on the surface of the sulfur-titanium niobium oxide composite material by plasma enhanced chemical vapor deposition method specifically comprises:
[0030] A sulfur-titanium niobium oxide composite material is placed inside a plasma generator cavity, and the air in the cavity is evacuated. When the internal vacuum degree is 10 to 30 Pa, heating is started. When the temperature of the muffle furnace is raised to 30 to 150° C., carbon source gas molecules of the benzene substance are introduced into the tube by volatilizing the benzene substance, and the radio frequency power is turned on and adjusted to a radio frequency power of 100 to 500 W. The reaction time is 5 to 30 minutes. After the reaction is completed, heating is stopped, and the air pressure in the tube is backfilled to the standard atmospheric pressure with argon gas. After the furnace is cooled, the carbon-coated sulfur-titanium niobium oxide composite positive electrode material is taken out.
[0031] Further preferably, a method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material comprises the following steps:
[0032] (1) uniformly mixing a titanium precursor with a purity of ≥98% and a niobium precursor with a purity of ≥99% in an organic solvent at room temperature, adding 3-5 wt.% of an additive, and magnetically stirring for 15-20 minutes, pouring the mixed solution into a polytetrafluoroethylene liner, and then placing the liner in a reactor to perform a solvent thermal reaction at a certain temperature for several hours;
[0033] (2) After the reactor is cooled to room temperature, the inner tank of the reactor is opened, and the obtained precipitate is washed with deionized water for 3 to 5 times and dried in a forced air drying oven for several hours, and then the material is transferred to a muffle furnace and calcined at a certain temperature for several hours to obtain a titanium niobium oxide material;
[0034] (3) uniformly mixing elemental sulfur and titanium niobium oxide in an organic solvent at room temperature, magnetically stirring for 10 to 15 minutes, pouring into a reactor with a polytetrafluoroethylene liner, and performing a solvent thermal reaction at a certain temperature for several hours. After the reaction, the reactor is opened, then filtered and dried for several hours to obtain a sulfur-titanium niobium oxide composite material;
[0035] (4) sealing a benzene-based carbon-containing precursor source in a glass container with a gas valve, placing the sulfur-titanium niobium oxide composite material obtained in step (3) in a plasma generator chamber, and coating the surface of the sulfur-titanium niobium oxide composite material with carbon material by plasma enhanced chemical vapor deposition to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounts for 67-88wt.%, the titanium niobium oxide accounts for 10-28wt.%, and the carbon element accounts for 2-5wt.% of the total composite positive electrode material.
[0036] In the present invention, the porous polar material titanium niobium oxide can achieve fast ion charge and discharge at high rates due to its excellent electrical conductivity. The porous structure can provide effective sulfur storage space for the titanium niobium oxide and elemental sulfur to compound, alleviating the volume expansion problem of sulfur during the charge and discharge process. 2 , Fe2 O 3 When combined with sulfur, although it can enhance the adsorption capacity of polysulfides and improve the cycle stability of lithium-sulfur batteries, it does not provide reversible charge and discharge capacity within the operating voltage range of lithium-sulfur batteries, which will lead to a decrease in the gram-specific capacity of the composite material, which is not conducive to improving the energy density of lithium-sulfur batteries. Titanium-niobium oxide materials have a high reversible specific capacity (387mAh / g) in the voltage range of 1V-3V. After being combined with sulfur, they can not only realize the adsorption of polysulfides by conventional metal oxide materials, but also provide additional capacity within the operating voltage range of lithium-sulfur batteries. Therefore, they can improve the cycle stability of the sulfur positive electrode and will not significantly reduce the energy density of lithium-sulfur batteries.
[0037] The present invention also provides a carbon-coated sulfur-titanium niobium oxide composite positive electrode material prepared by any one of the above preparation methods.
[0038] The present invention also provides an application of a carbon-coated sulfur-titanium niobium oxide composite positive electrode material prepared by any of the above preparation methods in the field of lithium metal batteries.
[0039] Based on the above technical solution, the present invention has the following beneficial effects:
[0040] (1) The titanium niobium oxide synthesized by the solvothermal method of the present invention is composed of a microsphere structure with a particle size of 2 to 8 μm, has a large specific surface area and a pore size distribution of less than 50 nm, provides a certain space for sulfur storage, and alleviates the problem of volume expansion during the discharge of elemental sulfur.
[0041] (2) The present invention effectively improves the conductivity of elemental sulfur by compounding elemental sulfur with titanium niobium oxide. At the same time, the material has a stronger adsorption effect on polysulfides, which improves the overall cycle stability of the material. The titanium niobium oxide material itself has a high discharge specific capacity, and after compounding with sulfur, it can provide a certain capacity support in the operating voltage range of the lithium-sulfur battery, and will not significantly reduce the battery energy density.
[0042] (3) The present invention uses plasma technology to coat the carbon material on the surface of the sulfur-titanium niobium oxide composite material with a thickness of 10 to 20 nm, and the composite positive electrode material has a low carbon content, which can significantly improve the electronic conductivity of the composite material, improve the rate performance of the lithium-sulfur battery and the charge and discharge efficiency of the battery, and has broad market application prospects.
[0043] (4) The present invention realizes carbon coating through plasma technology, which has a simple operation process, high efficiency and is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1is a SEM image of the titanium niobium oxide material in Example 1 of the present invention;
[0045] Figure 2 is a BET diagram of the titanium niobium oxide material before and after sulfur storage in Example 1 of the present invention;
[0046] Figure 3 is a pore volume and pore size distribution diagram of the titanium niobium oxide material in Example 1 of the present invention;
[0047] Figure 4 is a SEM image of the carbon-coated sulfur-titanium niobium oxide composite positive electrode material in Example 1 of the present invention;
[0048] Figure 5 It is a comparison diagram of the first charge and discharge curves of the two materials in Example 1 of the present invention and Comparative Example 1;
[0049] Figure 6 It is a cycle capacity diagram of two materials in Example 1 of the present invention and Comparative Example 2 at different rates. DETAILED DESCRIPTION
[0050] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0051] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0052] Example 1
[0053] (1) 0.945 g of tetrabutyl titanate (purity 98%), 1.5 g of niobium pentachloride (purity 99.9%) and 0.122 g of polyvinyl alcohol were mixed in an ethanol solution at room temperature 25°C, with a material-liquid mass ratio of 1:6, and magnetically stirred for 20 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 180°C for 14 h;
[0054] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed three times with deionized water and dried in a forced air drying oven at 60°C for 12 h. The material was then transferred to a muffle furnace and calcined at 850°C for 8 h to obtain a particle size and pore size of 3-6 μm and 2-30 nm, respectively, and a specific surface area of 300 m 2 / g of mesoporous titanium niobium oxide material;
[0055] (3) 0.8 g of elemental sulfur and 0.2 g of titanium niobium oxide were mixed in an ethanol solution at room temperature with a material-liquid mass ratio of 1:6, magnetically stirred for 10 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 160° C. for 16 h. After the reaction, the reactor was opened, filtered, and dried at 60° C. for 12 h to obtain a sulfur-titanium niobium oxide composite material;
[0056] (4) Toluene (carbon content of 91.3%) was sealed inside a glass container with an air valve, and the sulfur-titanium niobium oxide composite material obtained in step (3) was placed inside a plasma generator cavity, and the vacuum pump was turned on to evacuate the inside of the plasma generator cavity to maintain the cavity vacuum degree at 10 Pa. Then the plasma generator was turned on, and when the temperature inside the cavity reached 100° C., the radio frequency power supply was turned on, the radio frequency power was adjusted to 350 W, and the reaction was carried out under this condition for 10 minutes to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounted for 77wt.% of the total composite positive electrode material, the titanium niobium oxide accounted for 20wt.%, and the carbon element accounted for 3wt.%.
[0057] Example 2
[0058] (1) 0.945 g of tetrabutyl titanate (purity 98%), 1.5 g of niobium pentachloride (purity 99.9%) and 0.098 g of polystyrene were mixed in an ethylene glycol solution at room temperature 25°C, with a material-liquid mass ratio of 1:4, and magnetically stirred for 15 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 160°C for 14 h.
[0059] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed four times with deionized water and dried in a forced air drying oven at 80°C for 6 h. The material was then transferred to a muffle furnace and calcined at 900°C for 6 h to obtain a particle size and pore size of 4-5 μm and 5-44 nm, respectively, and a specific surface area of 174 m 2 / g of mesoporous titanium niobium oxide material;
[0060] (3) 0.9 g of elemental sulfur and 0.1 g of titanium niobium oxide were mixed in an ethylene glycol solution at room temperature with a material-liquid mass ratio of 1:4, magnetically stirred for 15 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 180 ° C for 12 h. After the reaction, the reactor was opened, filtered, and dried at 80 ° C for 10 h to obtain a sulfur-titanium niobium oxide composite material;
[0061] (4) Ethylbenzene (carbon content of 90.6%) was sealed in a glass container with an air valve, and the sulfur-titanium niobium oxide composite material obtained in step (3) was placed in the plasma generator cavity, and the vacuum pump was turned on to evacuate the plasma generator cavity to maintain the cavity vacuum degree at 30 Pa. Then the plasma generator was turned on, and when the temperature inside the cavity reached 80°C, the radio frequency power supply was turned on, the radio frequency power was adjusted to 300W, and the reaction was carried out under this condition for 15 minutes to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounted for 88wt.% of the total composite positive electrode material, the titanium niobium oxide accounted for 10wt.%, and the carbon element accounted for 2wt.%.
[0062] Example 3
[0063] (1) 1.26 g of tetrabutyl titanate (purity 98%), 2 g of niobium pentachloride (purity 99.9%) and 0.098 g of polylactic acid were mixed in an ethanol solution at room temperature 25°C, with a material-liquid mass ratio of 1:8, and magnetically stirred for 20 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 140°C for 20 h.
[0064] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed 5 times with deionized water and dried in a forced air drying oven at 120°C for 1 h. The material was then transferred to a muffle furnace and calcined at 750°C for 9 h to obtain a particle size and pore size of 3-6 μm and 10-50 nm, respectively, and a specific surface area of 137 m 2 / g of mesoporous titanium niobium oxide material;
[0065] (3) 0.8 g of elemental sulfur and 0.2 g of titanium niobium oxide were mixed in a carbon disulfide solution at room temperature with a material-liquid mass ratio of 1:8, magnetically stirred for 10 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 140 ° C for 20 h. After the reaction, the reactor was opened, filtered, and dried at 80 ° C for 12 h to obtain a sulfur-titanium niobium oxide composite material;
[0066] (4) Ethylbenzene (carbon content of 90.6%) was sealed in a glass container with an air valve, and the sulfur-titanium niobium oxide composite material obtained in step (3) was placed in the plasma generator cavity, and the vacuum pump was turned on to evacuate the plasma generator cavity to maintain the cavity vacuum degree at 15 Pa. Then the plasma generator was turned on, and when the temperature inside the cavity reached 120° C., the radio frequency power supply was turned on, the radio frequency power was adjusted to 400 W, and the reaction was carried out under this condition for 5 minutes to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounted for 78wt.% of the total composite positive electrode material, the titanium niobium oxide accounted for 20wt.%, and the carbon element accounted for 2wt.%.
[0067] Example 4
[0068] (1) 0.424 g of tetraethyl titanate (purity 99%), 2 g of niobium oxalate (purity 99%) and 0.121 g of polyvinyl alcohol were mixed in a butanol solution at room temperature 25°C, with a material-liquid mass ratio of 1:4, and magnetically stirred for 20 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 180°C for 8 h.
[0069] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed three times with deionized water and dried in a forced air drying oven at 60°C for 12 h. The material was then transferred to a muffle furnace and calcined at 900°C for 5 h to obtain a particle size and pore size of 3-8 μm and 3-32 nm, respectively, and a specific surface area of 259 m 2 / g of mesoporous titanium niobium oxide material;
[0070] (3) 0.7 g of elemental sulfur and 0.3 g of titanium niobium oxide were mixed in an isopropanol solution at room temperature with a material-liquid mass ratio of 1:4, magnetically stirred for 15 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 150 ° C for 24 h. After the reaction, the reactor was opened, filtered, and dried at 100 ° C for 5 h to obtain a sulfur-titanium niobium oxide composite material;
[0071] (4) Toluene (with a carbon content of 91.3%) was sealed inside a glass container with an air valve, and the sulfur-titanium niobium oxide composite material obtained in step (3) was placed inside a plasma generator cavity, and the vacuum pump was turned on to evacuate the inside of the plasma generator cavity to maintain the cavity vacuum degree at 20 Pa. Then the plasma generator was turned on, and when the temperature inside the cavity reached 150° C., the radio frequency power supply was turned on, the radio frequency power was adjusted to 100 W, and the reaction was carried out under this condition for 15 minutes to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounted for 67wt.% of the total composite positive electrode material, the titanium niobium oxide accounted for 28wt.%, and the carbon element accounted for 5wt.%.
[0072] Example 5
[0073] (1) 0.318 g of tetraethyl titanate (purity 99%), 1.5 g of niobium oxalate (purity 99%) and 0.073 g of polystyrene were mixed in an isopropanol solution at room temperature 25°C, with a material-liquid mass ratio of 1:4, and magnetically stirred for 15 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 180°C for 16 h.
[0074] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed three times with deionized water and dried in a forced air drying oven at 80°C for 8 h. The material was then transferred to a muffle furnace and calcined at 700°C for 10 h to obtain a particle size and pore size of 2-5 μm and 7-42 nm, respectively, and a specific surface area of 158 m 2 / g of mesoporous titanium niobium oxide material;
[0075] (3) 0.8 g of elemental sulfur and 0.2 g of titanium niobium oxide were mixed in an ethanol solution at room temperature with a material-liquid mass ratio of 1:4, magnetically stirred for 15 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 160° C. for 20 h. After the reaction, the reactor was opened, filtered, and dried at 60° C. for 14 h to obtain a sulfur-titanium niobium oxide composite material;
[0076] (4) Toluene (with a carbon content of 91.3%) was sealed inside a glass container with an air valve, and the sulfur-titanium niobium oxide composite material obtained in step (3) was placed inside a plasma generator cavity, and the vacuum pump was turned on to evacuate the inside of the plasma generator cavity to maintain a vacuum degree of 10 Pa. The plasma generator was then turned on, and when the temperature inside the cavity reached 30° C., the radio frequency power supply was turned on, the radio frequency power was adjusted to 500 W, and the reaction was carried out under this condition for 10 minutes to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounted for 78wt.% of the total composite positive electrode material, the titanium niobium oxide accounted for 19wt.%, and the carbon element accounted for 3wt.%.
[0077] Example 6
[0078] (1) 0.945 g of tetrabutyl titanate (purity 98%), 1.5 g of niobium pentachloride (purity 99.9%) and 0.073 g of polyvinyl alcohol were mixed in an ethanol solution at room temperature 25°C, with a material-liquid mass ratio of 1:6, and magnetically stirred for 20 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 180°C for 12 h;
[0079] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed three times with deionized water and dried in a 60°C forced air drying oven for 12 h. The material was then transferred to a muffle furnace and calcined at 800°C for 10 h to obtain a particle size and pore size of 4-5 μm and 1-36 nm, respectively, and a specific surface area of 254 m 2 / g of mesoporous titanium niobium oxide material;
[0080] (3) 0.9 g of elemental sulfur and 0.1 g of titanium niobium oxide were mixed in a butanol solution at room temperature with a material-liquid mass ratio of 1:6, magnetically stirred for 10 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 160° C. for 16 h. After the reaction, the reactor was opened, filtered, and dried at 60° C. for 10 h to obtain a sulfur-titanium niobium oxide composite material;
[0081] (4) Toluene (with a carbon content of 91.3%) was sealed inside a glass container with an air valve, and the sulfur-titanium niobium oxide composite material obtained in step (3) was placed inside a plasma generator cavity, and the vacuum pump was turned on to evacuate the inside of the plasma generator cavity to maintain the vacuum degree of the cavity at 15 Pa. Then the plasma generator was turned on, and when the temperature inside the cavity reached 60°C, the radio frequency power supply was turned on, the radio frequency power was adjusted to 200 W, and the reaction was carried out under this condition for 30 minutes to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, wherein the sulfur element accounted for 85wt.% of the total composite positive electrode material, the titanium niobium oxide accounted for 10wt.%, and the carbon element accounted for 5wt.%.
[0082] Comparative Example 1
[0083] The positive electrode material is made of elemental sulfur without any treatment.
[0084] Comparative Example 2
[0085] (1) 0.945 g of tetrabutyl titanate (purity 98%), 1.5 g of niobium pentachloride (purity 99.9%) and 0.098 g of polylactic acid were mixed in an ethanol solution at room temperature 25°C, with a material-liquid mass ratio of 1:6, and magnetically stirred for 20 min. The mixed solution was poured into a polytetrafluoroethylene liner, and then the liner was placed in a high-pressure reactor and subjected to a solvothermal reaction at 180°C for 14 h;
[0086] (2) After the reactor was cooled to room temperature, the reactor liner was opened, and the precipitate was washed three times with deionized water and dried in a forced air drying oven at 60°C for 12 h. The material was then transferred to a muffle furnace and calcined at 900°C for 8 h to obtain a particle size and pore size of 3-6 μm and 5-41 nm, respectively, and a specific surface area of 100 m 2 / g of mesoporous titanium niobium oxide material;
[0087] (3) 0.8 g of elemental sulfur and 0.2 g of titanium niobium oxide were mixed in an ethanol solution at room temperature with a material-liquid mass ratio of 1:6, magnetically stirred for 10 min, poured into a high-pressure reactor with a polytetrafluoroethylene liner, and subjected to a solvothermal reaction at 160° C. for 14 h. After the reaction, the reactor was opened, filtered, and dried at 60° C. for 12 h to obtain a sulfur-titanium niobium oxide composite material, in which sulfur accounted for 80 wt.% of the total composite positive electrode material and titanium niobium oxide accounted for 20 wt.%.
[0088] Battery assembly and performance testing
[0089] (1) Weigh 0.8g of the carbon-coated sulfur-titanium niobium oxide composite positive electrode material obtained in Example 1, 0.1g of conductive carbon black (Super P, particle size 40nm, purity 99.9%, Aladdin), 0.1g of binder PVDF (particle size 5μm, purity 99.9%, Aladdin) and 2.33g of solvent N-methylpyrrolidone (analytical grade, purity>99.0%, Aladdin) and place them in a glass bottle. Homogenize twice at a speed of 1780r / min on a homogenizer to obtain a positive electrode slurry with moderate viscosity. Finally, use a 150μm scraper to evenly scrape it on the surface of the aluminum foil, place it in a blast oven, and dry it at 60°C for 12h to obtain a carbon-coated sulfur-titanium niobium oxide composite positive electrode material positive electrode sheet.
[0090] Examples 2 to 6 and Comparative Examples 1 and 2 all prepared positive electrode sheets using the above method.
[0091] (2) The positive electrode sheet in step (1) was subjected to rolling and punching processes under the same conditions to obtain a positive electrode sheet with a diameter of 12 mm. In a glove box with humidity and oxygen concentration below 0.01 ppm and filled with argon gas, the positive electrode shell, positive electrode sheet, separator (Celgard 2400 type), electrolyte (1M LiTFSI + DOL: DME (volume ratio 1:1) + 2wt.% LiNO 3 ), lithium sheet, gasket, spring and negative electrode shell to assemble the battery. Finally, place it on the button battery sealing machine at 50kg / cm 2 After sealing the battery with the sealing pressure of 100%, leave it overnight.
[0092] (3) Place the button batteries with different positive electrodes that have been placed overnight in step (2) on a battery charge and discharge tester. The charge and discharge test voltage is 1.7 to 2.8 V, and the rate test current is 0.1C, 0.2C, 0.5C, 1C, and 2C.
[0093] Titanium niobium oxide material was prepared according to the above method. The results are shown in Table 1.
[0094] Table 1 Comparison of surface morphology of different titanium niobium oxide materials
[0095]
[0096] The porous structure of titanium niobium oxide prepared by solvothermal reaction has a structure larger than 100 m 2 / g specific surface area, particle size is 2-8μm, and the pore size of the prepared titanium niobium oxide material is mesoporous, thus providing a certain space for subsequent sulfur storage. The specific surface area of titanium niobium oxide after sulfurization is significantly reduced, indicating that elemental sulfur enters the pores of titanium niobium oxide through melting and diffusion.
[0097] The battery performance was prepared and measured according to the above method. The results are shown in Table 2.
[0098] Table 2 Comparison of electrochemical performance of different carbon-coated sulfur-titanium niobium oxide composite cathode materials
[0099]
[0100]
[0101] The carbon-coated sulfur-titanium niobium oxide composite positive electrode material in Example 1 was cycled at 0.1C in the first cycle, and the initial discharge capacity was 1156.12 mAh / g, and the first coulombic efficiency was 93.1%. Even under the condition of 2C high rate, the battery capacity was still as high as 525.97 mAh / g. The performance of Examples 2-6 has the same trend as that of Example 1. In Comparative Examples 1 and 2, pure elemental sulfur and sulfur-titanium niobium oxide positive electrode materials without carbon coating have lower discharge capacity and low coulombic efficiency, and have low capacity and battery short circuit at high rates. Therefore, the carbon-coated sulfur-titanium niobium oxide composite positive electrode material has a complete coating structure, which significantly improves the overall conductivity of the material and has excellent rate performance.
[0102] The embodiments described above are only preferred solutions of the present invention and are not intended to limit the present invention in any form. There are other variations and modifications without exceeding the technical solutions described in the claims. These changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material, characterized in that: The steps include: (1) uniformly mixing a titanium precursor and a niobium precursor in an organic solvent, adding an additive, and performing a solvothermal reaction; (2) calcining the obtained precipitate to obtain titanium niobium oxide material; (3) uniformly mixing elemental sulfur and titanium niobium oxide material in an organic solvent, and performing a solvothermal reaction to obtain a sulfur-titanium niobium oxide composite material; (4) Using benzene as a carbon source, a carbon material is coated on the surface of a sulfur-titanium niobium oxide composite material by a plasma method to prepare a carbon-coated sulfur-titanium niobium oxide composite positive electrode material.
2. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: In step (1), the titanium precursor is at least one of tetrabutyl titanate and tetraethyl titanate; the niobium precursor is at least one of niobium pentachloride and niobium oxalate; the additive is at least one of polystyrene, polyvinyl alcohol and polylactic acid; the amount of the additive is 3 to 5 wt.% of the total mass of the titanium precursor and the niobium precursor.
3. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: In step (1), the conditions of the solvent thermal reaction are: the organic solvent is at least one of ethanol, ethylene glycol, isopropanol and butanol, the reaction temperature is 140-180° C., the reaction time is 8-20 hours, and the material-liquid mass ratio is 1:4-1:
8.
4. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: In step (2), the calcination conditions are: calcination temperature is 700-900° C., calcination time is 5-10 hours, and heating rate is 2-5° C. / min.
5. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: The specific surface area of the titanium niobium oxide material is 100 to 300 m 2 / g, the pore size is 1 to 50 nm, and the particle size is 2 to 8 μm.
6. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: In step (3), the mass ratio of elemental sulfur to titanium niobium oxide is 7:3-9:1, and the conditions of the solvent thermal reaction are: the organic solvent is at least one of ethanol, ethylene glycol, isopropanol, butanol and carbon disulfide, the reaction temperature is 140-180°C, the reaction time is 12-24h, and the material-liquid mass ratio is 1:4-1:
8.
7. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: In step (4), the carbon source is at least one of benzene, toluene, ethylbenzene and xylene, and the plasma carbon coating reaction conditions include: evacuating to a vacuum degree of 10 to 30 Pa, heating temperature of 30 to 150° C., RF power of 100 to 500 W, and reaction time of 5 to 30 min.
8. The method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to claim 1, characterized in that: In step (4), the carbon content of the carbon-coated sulfur-titanium niobium oxide composite positive electrode material is 2 to 5 wt.%.
9. A carbon-coated sulfur-titanium niobium oxide composite positive electrode material prepared according to the method for preparing a carbon-coated sulfur-titanium niobium oxide composite positive electrode material according to any one of claims 1 to 8.
10. Application of a carbon-coated sulfur-titanium niobium oxide composite positive electrode material prepared by the preparation method according to any one of claims 1 to 8 in the field of lithium metal batteries.
Citation Information
Patent Citations
Transition metal sulfide coated with carbon, preparation method and application
CN104835961A
Preparation method of lithium ion battery novel cathode material Fe3O4 / Ni / C
CN104993125A
Preparation method of titanium-iron-niobium oxide electrode
CN116040686A
Negative electrode material and preparation method thereof, secondary battery and electric equipment
CN116093277A
Positive electrode active material for secondary battery, manufacturing method thereof, positive electrode for secondary battery arranged by use thereof, and secondary battery
JP2024007364A